THE ACTIVITY TEST OF BIDARA LEAF ETHANOL EXTRACT (ZIZIPHUS MAURITIANA) TOWARDS ESCHERICHIA COLI BACERIA (Journal of Health, Technology and Science (JHTS), 2023)
This research aims at investigating the antibacterial activity and optimum concentration of the ethanol extract of bidara leaves (Ziziphus mauritiana) against Escherichia coli bacteria. The method used in this research is a completely randomized design (CRD) consisting of 7 treatments and 4 replicates. The treatments are: P1 (negative control Aquades), P2 (10% concentration), P3 (12.5% concentration), P4 (15% concentration), P5 (17.5% concentration), P6 (20% concentration), and P7 (positive control Ciprofloxacin). The findings reveal that the concentration of ethanol extract of bidara leaves (Ziziphus mauritiana) has activity in inhibiting the growth of Escherichia coli bacteria. From the results of Kruskall-Wallis statistical analysis with a significant value of 0.003 or < 0.05, it appears that there is a dose of ethanol extract of bidara leaves (Ziziphus mauritiana) that affects the growth of Escherichia coli bacteria. After further testing (Duncan test), it was found that there was no significant difference between one concentration and another, so it can be said that the optimum concentration of bidara leaf ethanol extract treatment (Ziziphus mauritiana) in inhibiting the growth of Escherichia coli bacteria is at a concentration of 10%.